A rapid assessment of migrant careworkers' psychosocial status during Israel's COVID-19 lockdown - Jordan Hannink Attal; Ido Lurie; Yehuda Neumark (BMC, 2020)
Abstract Background Israel hosts nearly 70,000 migrant careworkers. Migrant careworkers work and live with populations extremely vulnerable to the novel Coronavirus, including the elderly and people with pre-existing physical conditions. This rapid assessment aimed to explore psychosocial status and mental wellbeing of migrant careworkers in Israel during the ongoing Covid-19 pandemic and determine risk and protective factors associated with mental distress, anxiety, and depression. Methods This quantitative study was conducted via an online survey. The online survey collected social and demographic data, including country of origin, residence, age, sex, and time in Israel. In addition, questions were asked about knowledge of COVID-19 guidelines, access to supplies, and COVID-related racism. Respondents also completed a psychosocial screening tools, the Hopkins Symptom Checklist-10 (HSCL-10), which was used to screen for depression and anxiety. Results As of May 3rd, 2020, 307 careworkers responded to the online survey, of whom 120 (39.1%) were found symptomatic using the HSCL-10. Separating the HSCL-10 into subscales, 28.0% were symptomatically anxious, and 38.1% were symptomatic for depression. In multivariate regression, emotional distress was associated with household food insecurity (OR: 5.85; p < 0.001), lack of confidence to care for oneself and employer during the pandemic (OR: 3.85; p < 0.001), poorer general health (OR: 2.98; p < 0.003), non-Philippine country of origin (OR: 2.83; p < 0.01), female sex (OR: 2.34; p < 0.04),, and inversely associated with age (p < 0.03). While 87.6% of careworkers reported having access to hand sanitization materials regularly, only 58.0% had regular access to a medical grade mask, and 21.5% reported household food insecurity. Moreover, 40.0% of careworkers claimed to lack confidence to care for themselves and their employer during the COVID-19 pandemic. Conclusions Migrant careworkers exhibited high levels of mental distress during the COVID-19 lockdown, associated with lack of confidence or resources to properly care for themselves and their employer. Guidelines and support programs specific to the carework sector, that respect their rights and guard their health, must be developed as part of a coordinated COVID-19 response.